97.1k views
1 vote
Imagine you derive the following expression by analyzing the physics of a particular system: M= (mv2r)(mGr2). Simplify the expression for M using the techniques mentioned above.

1 Answer

3 votes

Answer:

The simplified expression is
M = (v^2 r)/(G)

Step-by-step explanation:

From the question we are told that


M = ( (m v^2)/(r) )/(( mG)/(r^2 ) )

So simplifying we have


M = (m v^2)/(r) * (r^2 )/( mG )


M = (v^2 r)/(G)

Thus the simplified formula is
M = (v^2 r)/(G)

User Karlo Kokkak
by
5.1k points